Towards a definition of Web 2.0 - a comparative study of the 'wiki', 'blog' and 'social network' as instances of Web 2.0 - Lewis, Belinda Ann (My University, 2009)
Web 2.0 was a phrase coined in 2004 to describe the characteristics of web sites which survived the original Dot-com crash. Despite the discussion of this phenomenon in a wide variety of both academic and mass media sources, itʼs exact definition remains unclear. The relative contributions of technology and social participation to this phenomenon are particularly confused. The primary aim of this research report is to provide a clear and comprehensive definition of Web 2.0. This definition is determined through a combined social and technological analysis of blogs, wikis and social network sites, through their particular manifestations in Boing Boing, Wikipedia and Facebook respectively. It is the finding of this research that Web 2.0 is primarily the result of a natural evolution from Web 1.0 technologies and attitudes, and that Web 2.0 is essentially a social phenomenon. This research provides separate definitions for Web 2.0 technologies and Web 2.0 platforms. A Web 2.0 technology is any technology that aids and encourages simple intuitive user interaction through an architecture of participation. These technologies enable user feedback, and are thus constantly improved and exist within the ethos of a perpetual beta. Web 2.0 technologies embrace re-mix and mash-up philosophies. A Web 2.0 platform is a read-write Web platform designed to enable and encourage User Generated Content and interaction. These platforms can be built with any set of technologies, and their primary characteristics are social in nature, but the platforms must allow users to interact with the technology at either an open-source, network or appropriation level. These platforms become more powerful and richer the greater the number of people using the platform, and ultimately result in the formation of Web 2.0 communities.
Keywords: Web 2.0, social network, blog, wiki, Facebook, Wikipedia